A Review of Emotions in Human-Robot Interaction - Ottoni, Lara Toledo Cordeiro; Cerqueira, Jés de Jesus Fiais (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
In human-robot interaction (HRI) it is important that the robot recognizes the emotions of humans and that it is able to transmit emotions, making the interaction between the human and the robot natural and empathic. This article aims to search the literature on human-robot interactions using emotion. For this, 72 articles from the literature were selected. Of these, 30% had as their main objective the development of methods for detecting emotions in humans, such as the recognition of emotions by facial expression, speech, touch or physiological signals. Another 70% of the papers analyzed the best way to represent emotions in robots so that the HRI was natural and friendly. In addition, perspectives for future work for the area are presented.